TINJAUAN WARNA PADA RUANG SEBAGAI SARANA RELAKSASI PADA FOREST HILLS HOTEL CIWIDEY - Rahimah, Yasmin Nur; Zein, Anastasha (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2025)
Increased work pressures and hectic activities in urban environments often cause stress and reduce people's quality of life. One of the most effective ways to relieve stress is through a staycation, which is a short vacation by staying at a hotel not far from where you live. Deluxe Executive Indoor Balcony rooms are designed with interiors that support tranquility and comfort. This study aims to evaluate the visual elements in interior design that can create an atmosphere of relaxation. The method used is qualitative, with data obtained from literature studies in the form of books, documents, and research reports. The results of the analysis show that visual elements such as color, materials, lighting, and scenery have an important role in shaping a relaxing space. Although there are still things that need to be improved, the design of this room has provided a relaxing stay. The findings can serve as a reference in designing interiors that support mental health.